2017
DOI: 10.1186/s13287-017-0534-1
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation regulates myofibroblast differentiation of human skin fibroblasts

Abstract: BackgroundFibroblasts are key players in maintaining skin homeostasis and in orchestrating physiological tissue repair and skin regeneration. Dysfunctions in fibroblasts that occur with aging and the senescent process lead to the delayed healing observed in elderly people. The molecular mechanisms leading to fibroblast dysfunction during aging and the senescent process have not yet been clarified. Previously, changes in patterns of glycosylation were observed in fibroblasts in aging and the senescent process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Cells were harvested and dissociated as previously described using Accutase cell detachment solution (Merck Millipore). Dissociated single cells were incubated with rabbit polyclonal anti‐human CD133 (ab19898; Abcam) diluted in FACS buffer (0.5% [w/v] BSA and 0.1% [w/v] sodium azide in PBS) for 30 minutes on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested and dissociated as previously described using Accutase cell detachment solution (Merck Millipore). Dissociated single cells were incubated with rabbit polyclonal anti‐human CD133 (ab19898; Abcam) diluted in FACS buffer (0.5% [w/v] BSA and 0.1% [w/v] sodium azide in PBS) for 30 minutes on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Sialylation is a process of adding a terminal sialic acid (Sia) to the subterminal monosaccharide of carbohydrate chains on glycoproteins or glycolipids. It plays many roles in normal physiology, for example, neural differentiation [6], tissue regeneration [7,8], and resistance to influenza virus infection [9,10]. The increase of sialylation and sialylated-glycans were associated with development and progression of human diseases including cancer [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate antigens are widely expressed on the cell surfaces and in extracellular matrix (ECM) as components of different glycoproteins. They contribute significantly to many crucial, biological functions, such as cell differentiation, cell adhesion, cell-cell interactions, and regulation of signaling pathways (Sasaki et al 2017). Glycans of the human cells are mostly linked to serine/threonine or asparagine of polypeptide chains forming O-or N-glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts are essential in maintaining skin homeostasis and participate in physiological tissue repair and skin regeneration. It has been demonstrated that cell surface glycans on fibroblasts can be affected by different external factors, e.g., during aging (Sasaki et al 2017;Itakura et al 2016).…”
Section: Introductionmentioning
confidence: 99%